Sport spectatorship motives of Malaysian university students - Popa, Arporn; Yusof, Aminuddin; Mohd Shah, Parilah; Soh, Kim Geok (VictorQuest Publications, 2013)
The purpose of this study was to investigate Malaysian students’ sport spectatorship motives and to determine differences in motives in terms of gender and nationalities. Using Capella’s (2001) Fan Behavior Questionnaire, data was collected from 259 local and international students studying at Universiti Putra Malaysia. The result of t-tests (p < 0.05) suggests significant differences in motives between males an d females in terms of pro social behaviors (t = 3.308), anti-social behaviors (t = 4.104), and emotionality (t = 5.383). Local and international students differed significantly in terms of pro social behaviors dimension (t = 2.203, p < 0.05), but there was no significant difference in terms of negative behaviors and emotionality. The results of the study were discussed in light of earlier findings concerning motives of watching sports events.